The next generation space suit: a case study of the systems engineering challenges in space suit development - Cabrera, Michael A., author; Simske, Steve, advisor; Marzolf, Greg, committee member; Miller, Erika, committee member; Delgado, Maria, committee member (Colorado State University. Libraries, 2023)
The objective for a NASA contractor, the performing organization in this case study, is to develop and deliver the next generation space suit to NASA, the customer in this case study, against a radically different level of customer expectation from previous years. In 2019, the administration had proposed a return to the moon, thus transforming and changing the system context of the current, next generation space suit in addition to pushing schedule expectations forward two years. The purpose of this dissertation will serve as a case study in two specific areas with qualitative and quantitative analyses regarding a new process and approach to (i) project lifecycle development and (ii) requirements engineering with the intent that if utilized, these tools may have contributed to improvements across the project in terms of meeting cost, scope, budget and quality while appropriately accounting for risk management. The procedure entails a research method in which the current state of the project, current state of the art, and the identified systems engineering challenges are evaluated and iterative models are tempered through development by continual improvements by engineering evaluation of engineers on the project. The current results have produced (i) a prototype project lifecycle development method via agile, Lean and Scrum hybrid implementations into a Traditional Waterfall framework and (ii) a prototype requirements engineering scorecard with implementations of FMEA and quantitative analysis to determine root cause identification.
Keywords: NASA; requirements engineering; space suit; project management; INCOSE; Scrum